(3OQGSI CKQ GdfeW GdbjGOj dQDSGA GdOhGFQ GdCcGOejI Ydi JMajR GdeYdejf aj HYV eOGQS eMGaXI HjQhJs - (3CYjf, fOi SHYs ((3HjQhJs (3GdLGeYI GddHfGfjI (B- (3cdjI GdJQHjI, GdYeGOIs, 2008)
(3JfGhdJ gPg GdOQGSI CKQ GdfeW GdbjGOj dQDSGA GdOhGFQ GdCcGOjejI aj JMajR GdeYdejf aj KdGK eOGQS NGUI aj eMGaXI HjQhJ, HGdEVGaI Gdi OQGSI YhGed JMajR cd ef QDSGA GdOhGFQ GdCcGOjejI hGdeYdejf ajgG(B. (3hbO gOaJ Edi GdcTa Yf GdYhGed GdeMaRI ddeYdejf HTcd YGe hef Ke JMOjO CKQ GdfeW GdbjGOj aj YedjI GdJMajR ef NdGd GdYjfI GdeMOOI ef CLd JMSjf YedjI EjLGO GdOGaY GdQFjSj deSGYOI GdeYdejf Ydi JNWj GdeUGYH GdJj JYJQVge(B. (3JfJej gPg GdOQGSI Edi GdHMK GdeSMj Gdcej HMjK Je EYOGO GSJHjGfjf HfGA Ydi GdEWGQ GdfXQj GdPj Je GSJNdGUg ef COHjGJ GdGOGQI GdJQHhjI, aJe JhLjg GdChd ddeYdejf aj GdeOGQS GdKdGK YjfI GdOQGSI aj Mjf Cf GdKGfj Je JhLjgg dQDSGA GdOhGFQ GdCcGOjejI(B. (3EJVM ef NdGd GdfJGFL hLhO JfhY hGVM aj YhGed JMajR GdeYdejf hQDSGA GdOhGFQ GdCcGOjejI(B. (3ceG HQR GNJdGa hGVM aj YhGed JMajR GdeYdejf Hjf OGFQI hCNQi aj GdeOQSI GdhGMOI hgPG eQOg Gdi GdfeW GdbjGOj GdPj jJHYg QFjS GdOGFQI GdCcGOjejI(B. (3hdcf JWGHbJ YhGed JMajR QDSGA GdOhGFQ GdCcGOjejI hYhGed JMajR GdeYdejf aj eQMdI ebGQfJgG Vef GdeOGQS GdKdGK dLgI GYJHGQ (B"(3GdTYhQ HGdCeGf hGdWeCfjfI(B" (3aj ebOeI eQGMd GdYhGed GdeMaRI dge ebGHd GYJHGQ (B"(3GdecGaBJ GdeGdjI(B" (3aj eDNQJgG(B.s
(3GdfhY (B: (3QSGdIs
Keywords: Beyrouth; Gestion scolaire; Incitation pour enseignant; Leadership; Leadership Beirut; Teachers incentives School management; (3GdbjGOI HjQhJs; (3OGaYjI GdeYdejf GdGOGQI GdeOQSjIs